Environmental Impact Assessment for Projects in the Nile Basin Countries - El Gohary, Rasha; Armanious, Sameh (European Scientific Journal, ESJ, 2017)
Environmental Impact Assessment (EIA) is a key aspect of many large-scale planning applications. It is a technique which is meant to help in understanding the potential environmental impacts of major development proposals. Unfortunately, the process and the outcome of EIA can be complex and confusing, leaving local communities unsure as to how a development might affect them. The objective of this research is to provide a strategic environmental framework for the environmentally sustainable development of the Nile River Basin, to improve the understanding of the relationship between water resources development and environmental conservation in the Basin, and to provide a forum to discuss development paths for the Nile with a wide range of stakeholders. Focusing on transboundary issues provides the riparian countries with a major opportunity to make significant progress towards their economic and environmental goals in ways that have proved difficult to achieve independently. In addition, the paper analyzes some EIAs carried into Egypt, which share the Nile as a common environmental resource with the other Nile basin countries, and discusses how improvements of guidelines and unification of legislation can improve cooperation among these countries. Finally, the paper recommends an EIA process revision to be implemented for effective EIA practice in the Nile Basin Countries.